2004
DOI: 10.1242/jcs.01279
|View full text |Cite
|
Sign up to set email alerts
|

Small hepatocytes in culture develop polarized transporter expression and differentiation

Abstract: SummarySmall hepatocytes in culture develop polarized transporter expression and differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Considering the fact that the upregulation of Mrp3 is often observed in cholestatic conditions, the cyst formation may release the pressure of accumulating bile in closed BC and create a flow directly to the cyst. Pfä ndler et al [2004] also demonstrated that time-dependent expression of individual transporters correlating with the maturation of SHs in growing colonies had some striking similarities with the ontogenesis of the hepatocellular bile-salt and organic-anion transport polarity. We have demonstrated that the SH is a committed hepatic progenitor cell that can further differentiate into an MH [Mitaka et al, 1999;Kon et al, 2006].…”
Section: Discussionmentioning
confidence: 81%
“…Considering the fact that the upregulation of Mrp3 is often observed in cholestatic conditions, the cyst formation may release the pressure of accumulating bile in closed BC and create a flow directly to the cyst. Pfä ndler et al [2004] also demonstrated that time-dependent expression of individual transporters correlating with the maturation of SHs in growing colonies had some striking similarities with the ontogenesis of the hepatocellular bile-salt and organic-anion transport polarity. We have demonstrated that the SH is a committed hepatic progenitor cell that can further differentiate into an MH [Mitaka et al, 1999;Kon et al, 2006].…”
Section: Discussionmentioning
confidence: 81%
“…A number of studies have previously investigated the in vitro hepatocyte differentiation in both mammals and freshwater fish (Ostrander et al 1995;Michalopoulos et al 1999;Mitaka et al 1999;Sidler Pfandler et al 2004;Yanhong et al 2008). Although, a number of studies on hepatocyte cultures have been carried out in freshwater species since long time, only discrete research has been performed on seabream liver, and none has been able to produce functionally active long cultured SaHePs expressing a mature phenotype (Mosconi et al 2002;Carnevali et al 2005;Bevelander et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of polarized transporters has been successfully investigated in rat SHs. These were found to be able to maintain a fully differentiated transporter expression phenotype during their transition into mature hepatocytes (Sidler Pfandler et al 2004). Here, we demonstrated that long term cultured SaHePs regain their specialized cytoarchitecture, while expressing a polarized phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In rat small hepatocytes, which are hepatocyte progenitor cells of the adult liver, Mrp1 mRNA levels are increased approximately 2-fold during 5–9 weeks in culture (Sidler Pfandler et al, 2004). Similarly, MRP1 mRNA expression is higher in hepatic oval cells than rat hepatocytes (Zhang et al, 2007a).…”
Section: Regulation Of Hepatic Abcc1/mrp1 Transporter By Xenobiotics mentioning
confidence: 99%